Posttraumatic Memories and Feelings of Guilt in Tim O’Brien’s The Things They Carried - Almasoudi, Ruwaida (Al-Adab Journal, 2023)
Writing has long been related to communicating emotional experiences. One of these experiences is war, and the Vietnam War was a long brutal struggle divided into two periods. The first is called the good Vietnam War, covering the years from 1964 to 1968. The second spanned from 1968 to 1972, known as the bad Vietnam War, through which fighting turned into guerilla war. Battles of the second phase were characterized by savage killings of soldiers and mass murder of unarmed civilian Vietnamese. This bad war inspired many literary narratives in drama, fiction, and poetry. Tim O’Brien’s The Things They Carried is considered one of the most read and vivid works about this struggle. The text reflects combatants’ engagements in foreign lands and their inability to adjust to the trauma after the war is over. The paper investigates the situations of various characters in the novel and how their experiences were influential in preventing them from normally continuing with their lives. Post-traumatic memories and permanent feelings of guilt and confusion are the main obstacles veterans face preempting them from indulging once again in society.